Nutrient digestibility of mulberry leaves(Morus alba) - Abdrazak Alimon; Riyadh A.Al-Kirshi; Idrus Zulkifli; Wan Zahari Mohamed (2013)
The current study was conducted to determine the chemical composition of mulberry (Morus alba) leaf meal (MLM) and its nutritive value as a feed ingredient. Fifteen layer and fifteen broiler chickens were used in the digestibility trial. The dry matter (DM), crude protein (CP), ash, fat (EE), crude fibre, neutral detergent fibre (NDF), acid detergent fibre (ADF), calcium (Ca), phosphorus (P) and gross energy (GE) content of MLM were analyzed. The precision-feeding technique was applied to feed the birds 30 g/kg DM of MLM. The results showed that MLM contained a high content of CP (29.8%), Ca (2.73%) and NDF (35.77%). Layers and broilers chicken could utilize 73% and 72% of CP, respectively, in MLM. The nutrient digestibility of DM and NDF was higher in layers than in broilers. No significant effect was observed in ME and other nutrient digestibility between the two classes of fowls. In general, the incorporation of MLM into the chickens’ diet could be a good source of protein despite its high fibre content.